Nutritional Content and Significance of Tomato Powder - Srivastava, Soma; Kulshreshtha, Kalpana (Annals of Arid Zone, 2016)
Tomatoes are known to be a rich source of vitamins, minerals and carotenoids, especially vitamin C, phosphorus, potassium, and lycopene and it may become an ideal addition to different types of processed foods. Keeping in view all these facts, dried tomato powder was prepared and analyzed for its vitamin C, lycopene and mineral contents. Tomato powder contain vitamin C 125 mg, lycopene 1.41 mg, iron 3.99 mg, phosphorus 173 mg, calcium 80 mg, magnesium 126 mg, Zinc 2.71 mg, copper 0.876 mg, manganese 1.83 mg, sodium 121.60 mg and potassium 2805.8 mg per 100 g. The results obtained showed that it is a good source of various macro and micro mineral elements. One hundred grams of tomato powder provides between 5.81-74.82% and 6.39-87.00% of the daily recommended intake for different macro and micro mineral elements for Indian male and female, respectively. Key words: Mineral, trace element, lycopene, daily recommended intake.